2009
DOI: 10.1002/bit.22271
|View full text |Cite
|
Sign up to set email alerts
|

In silico strategy to rationally engineer metabolite production: A case study for threonine in Escherichia coli

Abstract: Genetic engineering of metabolic pathways is a standard strategy to increase the production of metabolites of economic interest. However, such flux increases could very likely lead to undesirable changes in metabolite concentrations, producing deleterious perturbations on other cellular processes. These negative effects could be avoided by implementing a balanced increase of enzyme concentrations according to the Universal Method [Kacser and Acerenza (1993) Eur J Biochem 216:361-367]. Exact application of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Various applications are reported, such as optimization of synthesis of amino-acids (AA), [19][20][21][22] ethanol, [23][24] succinate, 25 lactate, 26 or other metabolites in mutant cells 27,28 . Deterministic simulation platforms allow in silico design of modified cells with desirable gene circuits and 'motifs' of practical applications in the biosynthesis industry, environmental engineering, and medicine.…”
Section: Department Of Chemical and Biochemical Engineering University mentioning
confidence: 99%
“…Various applications are reported, such as optimization of synthesis of amino-acids (AA), [19][20][21][22] ethanol, [23][24] succinate, 25 lactate, 26 or other metabolites in mutant cells 27,28 . Deterministic simulation platforms allow in silico design of modified cells with desirable gene circuits and 'motifs' of practical applications in the biosynthesis industry, environmental engineering, and medicine.…”
Section: Department Of Chemical and Biochemical Engineering University mentioning
confidence: 99%
“…The aim is, therefore, to develop approximate solutions, achieving similar results and requiring a smaller amount of work . It has been shown with a model of an E. coli Thr overproducing strain that manipulating a small number of the steps involved in the universal method may be sufficient to obtain a solution relatively close to the exact one. The MMM, developed in this work, was devised to determine, experimentally, where those key steps for manipulation are located in the network.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the exact application of the universal method requires changing a relatively high number of steps, which may be difficult to implement in practice. However, model simulation has shown that, of all the steps corresponding to the exact application of the method, it may be sufficient to manipulate only a small number of key steps to obtain the desirable flux increase . Strategies, previously developed, to determine these key steps are limited by restrictive assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous decrease of the limiting rates of HK and PFK, the enzymes controlling the flux, is equivalent to a minimal implementation with only two enzymes of multisite modulation, which is an efficient way by which organisms achieve very large flux changes, but with only small concentration changes in internal metabolites [37], [38], [39]. Fig.…”
Section: Discussionmentioning
confidence: 99%